Pacific marten (Martes caurina) as an apex predator : the habitat and diet ecology of an insular population of mesocarnivore on Haida Gwaii - Breault, David Norman (Author); Johnson, Christopher (Thesis advisor); Gillingham, Michael (Committee member); Todd, Melissa (Committee member); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2020)
Pacific marten (Martes caurina) may benefit from invasive or non-native species that occur across some coastal areas of the Pacific Northwest. I used remote-camera trapping and stable-isotopes of carbon and nitrogen to infer resource-use strategies of marten on Haida Gwaii, British Columbia, Canada. Marten are more likely to be detected in 3 ha patches with less logging and optimal amounts of road and forest edge habitat, and areas close to marine shorelines and streams. Findings from bulk carbon and nitrogen stable-isotope analysis suggest that terrestrial fauna, including birds, deer, small mammals, and invertebrates, contribute the most to diet; marine invertebrates are the second-most important prey group. Marten consume salmon and berries seasonally, but these are a relatively minor component of the diet. Knowledge of habitat and diet ecology of this generalist, apex predator should be integrated into ecosystem-based management and conservation of the globally rare old-growth forests that remain relatively intact on Haida Gwaii.